DESIGN OF FISHING SHIP MONITORING INFORMATION SYSTEM CASE STUDY IN THE MARINE AND FISHERY RESOURCES SUPERVISION UNIT - Romahdoni, Muhammad Reza; Kesuma, Mezan el-Khaeri; Mahesa, Muhammad Yusril; Hartabela, Dadang (Universitas Islam Negeri Raden Intan Lampung, 2022)
The Marine and Fishery Resources Supervision Work Unit (SATKER PSDKP) Lempasing Bandar Lampung is a Unit or Work Unit under the Jakarta Marine and Fishery Resources Supervision Base which is indirectly mandated by Law Number 45 of 2009 concerning amendments to Law number 31 of 2004 on fisheries. The web-based fishing boat monitoring application makes it easy for admins to find out the position of fishing boats and can send SMS Gateway messages to fishermen. Where the admin can detect the location of fishing boats by utilizing the android device used by fishermen and Google Maps Fire. This web-based monitoring is built using PHP, MySQL, GAMMU and bootstrap while the development method is Structured System Analysis and Design (SSAD). This monitoring will provide convenience for the Admin and the captain in detecting the location of the ship and the destination of the ship in looking for fish at sea